Impact of Drought‐Flood Abrupt Alternation on Vegetation Productivity in Karst and Non‐Karst Regions of Southern China - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (International Journal of Climatology, 2026)
Drought‐flood abrupt alternation (DFAA)—characterised by rapid transitions between drought and flood events—is an extreme compound natural hazard that threatens ecosystems, particularly in fragile environments such as karst regions. Soil moisture is a key indicator of surface hydrological processes, directly regulating vegetation growth and recovery. This study utilises the Standardised Soil Moisture Index (SSMI) to identify DFAA events and applies Granger causality analysis to reveal soil moisture‐vegetation interactions. The impact of DFAA on vegetation productivity is quantified, with a comparative analysis between karst and non‐karst regions in southern China. The results indicate that: (1) From 2000 to 2020, SSMI showed a significant upward trend. Drought‐to‐flood events were more frequent, intense, and longer in duration than flood‐to‐drought events. Both types of events also exhibited substantial spatial heterogeneity. (2) SSMI and NDVI were positively correlated, with the strongest correlation reaching 0.32 at a 60‐day lag. Bidirectional causality between SSMI and NDVI was predominant, affecting 49.24% of the study area. (3) Flood‐to‐drought events synergistically intensified drought–flood stress, whilst drought‐to‐flood events mitigated stress effects. Consequently, vegetation recovery was slower after flood‐to‐drought events, particularly in hydrologically vulnerable karst regions.